Antibacterial activity and mechanism of chelerythrine against Streptococcus agalactiae - Xin, Jige; Pu, Qiqi; Wang, Ruiying; Gu, Yeqing; He, Lin; Du, Xuan; Tang, Guowen; Han, Diangang (Frontiers in Veterinary Science, 2024)
Streptococcus agalactiae (S.agalactiae), also known as group B Streptococcus (GBS), is a highly infectious pathogen. Prolonged antibiotic usage leads to significant issues of antibiotic residue and resistance. Chelerythrine (CHE) is a naturally occurring benzophenidine alkaloid and chelerythrine chloride (CHEC) is its hydrochloride form with diverse biological and pharmacological activities. However, the antibacterial mechanism of CHEC against GBS remains unclear. Thus, this study aims to investigate the in vitro antibacterial activity of CHEC on GBS and elucidate its underlying mechanism. The antibacterial effect of CHEC on GBS was assessed using inhibitory zone, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC) assays, as well as by constructing a time-kill curve. The antibacterial mechanism of CHEC was investigated through techniques such as scanning electron microscopy (SEM) and transmission electron microscopy (TEM), measurement of alkaline phosphatase (AKP) activity, determination of Na+ K+, Ca2+ Mg2+—adenosine triphosphate (ATP) activity, observation of membrane permeability, and analysis of intracellular reactive oxygen species (ROS) and mRNA expression levels of key virulence genes. The results demonstrated that the inhibition zone diameters of CHEC against GBS were 14.32 mm, 12.67 mm, and 10.76 mm at concentrations of 2 mg/mL, 1 mg/mL, and 0.5 mg/mL, respectively. The MIC and MBC values were determined as 256 μg/mL and 512 μg/mL correspondingly. In the time-kill curve, 8 × MIC, 4 × MIC and 2 × MIC CHEC could completely kill GBS within 24 h. SEM and TEM analyses revealed significant morphological alterations in GBS cells treated with CHEC including shrinkage, collapse, and leakage of cellular fluids. Furthermore, the antibacterial mechanism underlying CHEC’s efficacy against GBS was attributed to its disruption of cell wall integrity as well as membrane permeability resulting in extracellular release of intracellular ATP, AKP, Na+ K+, Ca2+ Mg2+. Additionally CHEC could increase the ROS production leading to oxidative damage and downregulating mRNA expression levels of key virulence genes in GBS cells. In conclusion, CHEC holds potential as an antimicrobial agent against GBS and further investigations are necessary to elucidate additional molecular mechanisms.